Propaganda and representation: analyzing conceptual definitions: Propaganda and representation: analyzing conceptual definitions - Monteiro, Gustavo Feital (Caminhos da História, 2022)
This article seeks to study the definition of the concepts of representation and advertising, in order to outline the limits of performance of each word. For this activity, the analyzes of certain authors will be observed, whose studies demonstrate the fundamental theoretical bases of both, to later carry out the comparison of the individual meanings and point out their approximations or divergences. Each term has a large space for debate with different positions among academics, which makes it difficult to establish stable research parameters. In contrast to the definitions formed by different researchers, this study seeks to clarify the thoughts and practices pointed out in history that would correspond with one concept or the other, facilitating the exercise of its analytical identification together with the deepening of the observation of its effects in the narrative of the past. Thus, the purpose of this analysis is to identify how the concepts share methodological characteristics in the observation of society, highlighting the relevance of both for the exercise of historical research and seeking to encourage a deeper approach to both by historiography.